Silencing SlMED18, tomato Mediator subunit 18 gene, restricts internode elongation and leaf expansion - Wang, Yunshu (Sci Rep, 2018)
Mediator complex, a conserved multi-protein, is necessary for controlling RNA polymerase II (Pol II) transcription in eukaryotes. Given little is known about them in tomato, a tomato Mediator subunit 18 gene was isolated and named SlMED18. To further explore the function of SlMED18, the transgenic tomato plants targeting SlMED18 by RNAi-mediated gene silencing were generated. The SlMED18-RNAi lines exhibited multiple developmental defects, including smaller size and slower growth rate of plant and significantly smaller compound leaves. The contents of endogenous bioactive GA(3) in SlMED18 silenced lines were slightly less than that in wild type. Furthermore, qRT-PCR analysis indicated that expression of gibberellins biosynthesis genes such as SlGACPS and SlGA20x2, auxin transport genes (PIN1, PIN4, LAX1 and LAX2) and several key regulators, KNOX1, KNOX2, PHAN and LANCEOLATE(LA), which involved in the leaf morphogenesis were significantly down-regulated in SlMED18-RNAi lines. These results illustrated that SlMED18 plays an essential role in regulating plant internode elongation and leaf expansion in tomato plants and it acts as a key positive regulator of gibberellins biosynthesis and signal transduction as well as auxin proper transport signalling. These findings are the basis for understanding the function of the individual Mediator subunits in tomato.